Initiation in the New High School: teaching practice at a public school in Salvador (2024) (Olhar de Professor, 2025)
This article aims to analyze the pedagogical experience developed in the Scientific Initiation course, a component of the formative itineraries of the New High School, at a public school in Salvador, Bahia, during the 2024 academic year. The course was designed to foster critical thinking, intellectual autonomy, and youth protagonism through the development of research projects. The study, conducted with two second-year classes, adopted a qualitative approach based on content analysis. The results indicate that Scientific Initiation can contribute to the development of investigative skills, the appreciation of academic writing, and the strengthening of student autonomy, while also revealing challenges related to curricular structure and teaching methodologies. It is concluded that the discipline constitutes a strategic space for critical education in High School, provided that adequate conditions for its implementation are ensured.